단수수 시럽 제조효율 향상을 위한 착즙액 고온처리 및 이화학적 특성 변화 - 황엄지(Eom-Ji Hwang); 이영훈(Yeong-Hoon Lee); 차영록(Young-Rok Cha); 권다은(Da-Eun Kwon); 박진천(Jin-Cheon Park) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2021)
본 연구에서는 단수수 시럽 제조효율을 높이고 품질을 향상시키기 위해 단수수 착즙액을 고온처리하여 불순물 생성 정도를 확인하고, 고온처리에 따른 착즙액의 이화학적 특성을 분석하였다. 고온처리 후 착즙액의 불순물 함량은 110°C(2시간), 120°C(30분, 1시간) 처리에서 7.0~7.5 mg/100 g으로 가장 높게 나타났다. 120°C(2시간), 130°C(30분, 1시간, 2시간) 처리에서 가열 온도와 시간이 증가할수록 불순물 함량이 감소하였다. 착즙액의 당도는 130°C(30분, 1시간, 2시간) 처리에서 무처리 대비 당도가 낮아졌으며, pH는 온도가 높아질수록 낮아지는 경향을 보였다. 갈색도는 가열 온도와 시간이 증가할수록 증가하였다. 유리당 함량은 착즙액 가열 온도와 시간이 증가할수록 fructose와 glucose 함량이 증가하였지만, sucrose 함량은 감소하는 경향을 나타냈다. 종합해보면 단수수 착즙액을 120°C에서 30분~1시간 처리했을 때 착즙액의 불순물 제거효율이 가장 높으며, 불순물을 제거한 착즙액을 이용하여 단수수 시럽 제조 시 품질 향상에 영향을 줄 것으로 판단된다. Sugar is essential for maintaining human life. However, excessive consumption of refined sugar causes obesity and diabetes. Recently, the demand for natural sugar is increasing. In this study, extracted sweet sorghum juice was first treated at high temperature to remove impurities and produce high-quality sweet sorghum syrup, and its physicochemical properties were analyzed by various temperature ranges. While purifying the sweet sorghum juice at various temperatures, the quantum of impurities was observed to be highest at 120°C and decreased at 130°C. The correlation between the sugar content and pH of the sweet sorghum juice was investigated, and the pH decreased as the temperature increased. In addition, the higher the reaction temperature and the longer the reaction time, the higher the juice’s brownness and the higher the content of fructose and glucose. At the same time, sucrose content was reduced. Finally, the sweet sorghum juice should be treated at 120°C for 30 minutes to 1 hour to attain the highest efficiency in removing impurities and to improve the quality of the sweet sorghum syrup. KCI Citation Count: 0